Abscisic acid plays a key role in the regulation of date palm fruit ripening - Elbar, Saar; Maytal, Yochai; David, Itzhak; Carmeli-Weissberg, Mira; Shaya, Felix; Barnea-Danino, Yaara; Bustan, Amnon; Harpaz-Saad, Smadar (Frontiers in Plant Science, 2023)
The date palm (Phoenix dactylifera L.) fruit is of major importance for the nutrition of broad populations in the world's desert strip; yet this crop is sorely understudied. Understanding the mechanisms regulating date fruit development and ripening is essential to customise this crop to the climatic change, which elaborates yield losses due to often too early occurring wet season. This study aimed to elucidate the mechanism regulating date fruit ripening. To that end, we followed the natural process of date fruit development and the effects of exogenous hormone application on fruit ripening in the elite cultivar ‘Medjool’. The results of the current study indicate that the onset of fruit ripening occurred once the seed had reached maximum dry weight. From this point, fruit pericarp endogenous abscisic acid (ABA) levels consistently increased until fruit harvest. The final stage in fruit ripening, the yellow-to-brown transition, was preceded by an arrest of xylem-mediated water transport into the fruit. Exogenous ABA application enhanced fruit ripening when applied just before the green-to-yellow fruit color transition. Repeated ABA applications hastened various fruit ripening processes, resulting in a significantly earlier harvest. The emerging pivotal role of ABA in the regulation of date fruit ripening is thoroughly discussed.